Supporting Volunteering Activities by Adults With Intellectual Disabilities: An Explorative Qualitative Study. Issue 4 (23rd October 2016) - Wicki, Monika T.; Meier, Simon
Abstract: A large number of adults with and without disabilities engage in volunteering activities, allowing them to meet new people, providing them with the opportunity to learn new skills, to build their confidence, and to contribute to society. However, in previous studies of volunteers with intellectual disabilities (ID), it has been shown that this group is rarely involved in volunteering. This study explores the challenges, opportunities, and support needs of such volunteers and develops a heuristic model to support volunteering by people with ID in Switzerland. Semistructured interviews were conducted with a convenience sample of six volunteers with ID. The analysis was based on reflexive grounded theory. Volunteering is one way in which people with ID can participate in society and receive recognition for their engagement. Basic needs, personal motivation, and social recognition are central for volunteers with ID. A heuristic model to support volunteering based on personal and social reasons of individuals with ID is developed. By receiving the appropriate support, people with ID can thus contribute by volunteering on the same terms as volunteers without disabilities. The present findings shed some light on ways to increase the rate of volunteering by people with ID. While the present model can help to identify the type of support appropriate for people with disabilities, future research should aim to verify the outcomes of this study in a larger sample.